Human papillomavirus and squamous cell carcinoma of the urinary bladder: DaBlaCa-10 study. (2nd November 2018) - Jørgensen, Kit Riegels; Høyer, Søren; Jakobsen, Jakob Kristian; Jensen, Thor Knak; Marcussen, Niels; Wrist Lam, Gitte; Hasselager, Thomas; Thind, Peter Ole; Toft, Birgitte Grønkær; Steiniche, Torben; Jensen, Jørgen Bjerggaard
Abstract: Objective: To evaluate a potential association between Human Papillomavirus (H.P.V.) and squamous cell carcinoma (S.C.C.) urinary bladder cancer (B.C.). Furthermore, the relation between p16INK4a, H.P.V. and B.C. was examined. Patients and methods: Patients were included and divided into three groups based on the histological diagnosis of B.C. specimens. An extensive exclusion was performed, including accepted casual risk factors for S.C.C. B.C., such as long-term use of catheters, cystolithiasis and Schistosoma hematobium infection. A total of 100 patients were included: 50 with pure S.C.C., 25 with urothelial carcinomas (U.C.) and 25 with squamous differentiation of U.C. (Sq.D.). The patients were operated at one of four major Danish hospitals in the period January 2005 to December 2016. Clinical information was collected from the medical records. Presence of H.P.V. was analyzed using the INNO-LiPA H.P.V. Genotyping Extra II. p16INK4a was analyzed using immunohistochemical (I.H.C.) staining. A p -value <0.05 was considered statistically significant. Results: An overall H.P.V. prevalence of 12/100 (12%) was observed. H.P.V. was demonstrated in 9/50 (18%) of the S.C.C. patients. Overall, p16INK4a over-expression was observed in 52/100 (52%) patients. However, concomitant H.P.V. positivity and p16INK4a over-expression were observed in only 4/100 (4%) patients. Conclusion: The presence of H.P.V. in one fifth of patients with S.C.C. B.C. was demonstrated. H.P.V. infection could have a significant association with S.C.C. B.C. without other known casual risk factors for S.C.C. B.C.